Impact of Corporate Reputation on Brand Segmentation Strategy: An Empirical Study from Iranian Pharmaceutical Companies: Impact of Reputation on Pharmaceutical Brand Segmentation - Afshin Vahabzadeh; Hossein Vatanpour; Rasoul Dinarvand; Ali Rajabzadeh; Jamshid Salamzadeh; Mehdi Mohammadzadeh (Iranian Journal of Pharmaceutical Sciences, 2017)
The impact of corporate reputation uses, including value creation, corporate communication, and strategic resources on branding strategies such as segmentation and producing intangible assets for different industries is investigated in western countries in the past few years, but there is a gap for the generalizability of findings to countries out of the United States and Europe. To establish the western researcher‟s external validity of theories in other countries and to obtain a better understanding of the influences of branding and corporate reputation in pharmaceutical business markets, the researchers applied this study for Iran, as a country in the Middle East. The obtained results using SEM (by P.L.S. 2.0 software) showed a weak relation between value creation and brand segmentation (β = 3.007 and t-value = 1.806) and no significant relation between corporate communication and strategic resources with brand segmentation (β = 0.199 and t-value = 1.301) and (β = 3.046 and t-value = 1.465). Based on these findings; and previous researches in this field, it seems that pharmaceutical managers and marketers need to change their thoughts and practices regarding segmentation and reputation.This study is a pioneering attempt in Iran to evaluate the impact of corporate reputation on brand segmentation strategy.